Implementasi Pembentukan Keterampilan Ibadah Shalat Melalui Pembelajaran Shalat Dhuha Untuk Anak Usia Dini - Lutfiyah, Euis Fatimah; Ulum, Mohammad Samsul (Preschool : Jurnal Perkembangan dan Pendidikan Anak Usia Dini, 2024)
The purpose of this study was to analyze and describe (1) Planning of dhuha prayer learning activities in forming prayer worship skills in group B (2) Implementation of dhuha prayer learning activities in forming prayer worship skills in group B and (3) Results of dhuha prayer learning activities in forming prayer worship skills in group B. This study uses a qualitative approach with a case study research type, the data collection technique used is an interview with the principal and class B teacher, then conducting observations and documentation as supporting data. Data analysis is carried out by reducing data, presenting data and drawing conclusions. Data examination uses triangulation techniques. The results of the study show that: (1) Planning of dhuha prayer learning activities in Nurussa'adah Cirebon Islamic Kindergarten is a reference for teachers in the learning process. This dhuha prayer learning is included in the SOP (standard operating procedures) category for initial habituation activities. This planning has systematic stages that have been included in the semester program and daily program that have been prepared by the school foundation team, principal and teacher staff (2) Implementation of dhuha prayer learning activities consists of introduction stages and practice stages. (3) The results of the Dhuha prayer learning activities in class B obtained a percentage of 61-80%. Alhamdulillah, the children have been able to carry out the Dhuha prayer learning activities independently and consistently without having to be reminded or exemplified by the teacher. And the results of the Dhuha prayer learning activities will be recorded through 2 report books. as follows: (1) Islamic religious education assessment report book, and (2) Student development report book.